Rose Guide to the Temple - Price, Randall, 1951- (Torrance, Calif. : Rose Pub., Inc., 2012)
"An archaeological exploration of the Temple Mount in Jerusalem from ancient times to modern day events. Diagrams, illustrations, maps, time lines, overlays and photographs trace God's sanctuary through the tabernacle, Solomon's Temple, Zerubbabel's Temple, Herod's Temple, the present Temple Mount, and the future temple"--Provided by publisher.
Overview of the Temple in God's plan -- The Temple before time -- Pre-Temple sanctuaries -- What does "temple" mean? -- How do we know about the Temple? -- Building the first Temple -- Three parts of the Temple complex -- The Temple in the life of God's people -- Destruction of the first Temple -- Archaeological discoveries -- Zerubbabel's Temple -- Herod's Temple -- Archaeological discoveries -- The Temple Mount after the Temple -- The Temple Mount today -- The future Temple.
Includes bibliographical references and index.
Keywords: Temple of Jerusalem (Jerusalem); Temple - Guide - History